Job Autonomy and Supervisor Work-Life Balance Support Impact on Work- Life Balance, Organizational Pride and Job Satisfaction in Surabaya and Jakarta - Shefry Frajonsky Simatauw (iBuss Management, 2021)
Work-life balance importance has yet to be recognized by Indonesians. Moreover, with the government decision on increasing the working hours, it might have disrupted the Indonesian work-life balance that is already below the global average. Work-life balance disruption would not only harm the employees, yet the company will also suffer from the impact. Two of the policies that companies can apply to prevent the disruption is job autonomy and supervisor work-life balance support. Therefore, the main purpose of this research is to see the impact of job autonomy and supervisor work-life balance support impact on work-life balance, organizational pride and job satisfaction. In the analysis, 238 data of employees working for companies located in Indonesia are analyzed with Partial Least Square – Structural Equation Modelling (PLS-SEM) in Smart PLS. The findings suggest that job autonomy and supervisor work-life balance support are positively affecting work-life balance, organizational pride as well as job satisfaction. Job autonomy and supervisor work-lifebalance support each only have a positive impact towards job satisfaction when mediated by work-life balance. Furthermore, work-life balance also positively affect job satisfaction. In addition, the relationship of work-life balance and job satisfaction is having a better impact when mediated by organizational pride.Keywords: Work-Life Balance, Job Satisfaction, Job Autonomy, Supervisor Work-Life Balance Support, Organizational Pride